2021
DOI: 10.31235/osf.io/vyrz7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Income Composition Inequality

Abstract: This paper examines the political determinants of income composition inequality in 32 advanced and emerging economies between 2006 and 2018. Income composition inequality is defined as the extent to which the income composition in capital and labor income is unevenly distributed across the income distribution. High levels of income composition inequality are associated with class-fragmented societies, whereas low levels are typical of multiple-sources-of-income societies. We find that a higher seat share of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…23 Third, a better understanding of the determinants of compositional inequality is necessary. Petrova and Ranaldi (2024) recently showed that left-wing parties tend to reduce, rather than increase, compositional inequality across the distribution within the context of Europe. However, evidence for the rest of the world is scarce, where different dynamics are certainly at play.…”
Section: Discussionmentioning
confidence: 99%
“…23 Third, a better understanding of the determinants of compositional inequality is necessary. Petrova and Ranaldi (2024) recently showed that left-wing parties tend to reduce, rather than increase, compositional inequality across the distribution within the context of Europe. However, evidence for the rest of the world is scarce, where different dynamics are certainly at play.…”
Section: Discussionmentioning
confidence: 99%
“…The study finds that DITRs, by lowering the marginal tax rate on capital income, contributed to capital income concentration and higher concentration at the top, which led to an increase in income composition inequality. Petrova and Ranaldi (2021) [3] argue that taxation and redistribution policies can have significant effects on income composition inequality. Specifically, they argue that tax reforms favoring capital income may shift capital income to the top of the income distribution, resulting in a more unequal distribution of income composition.…”
Section: Income Composition Inequality and Fiscal Redistributionmentioning
confidence: 99%
“…Drawing on Petrova and Ranaldi (2021) [3] and existing literature, the preceding section of this paper divides residents' income into two categories: capital income and labor income. The transfer payments are included in labor income while analyzing the redistributive effects.…”
Section: The Fiscal Redistribution Effects On Income Composition Ineq...mentioning
confidence: 99%
See 1 more Smart Citation
“…As for behavioral heterogeneity, seeDynan et al (2004),Saez and Zucman (2016),Jappelli and Pistaferri (2014),Bunn et al (2018) among others, whilst for endowment heterogeneity, seeRanaldi and Milanovic (2022),Iacono and Ranaldi (2022),Iacono and Palagi (2022b),Petrova and Ranaldi (2021),Berman and Milanovic (2020).…”
mentioning
confidence: 99%